2019
DOI: 10.1308/rcsann.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Is the laparoscopic approach a safe choice for the management of acute appendicitis in pregnant women? A meta-analysis of observational studies

Abstract: Introduction Acute appendicitis is a common and serious situation during pregnancy, because of the increased risk of fetal loss and perforation in the third trimester, as well as a diagnostic difficulty. During recent years laparoscopic approach has been introduced to clinical practice with encouraging results. The purpose of this meta-analysis is to compare the surgical and obstetrical outcomes between laparoscopic and open appendectomy during pregnancy. Materials and methods MEDLINE, SCOPUS, Clinicaltrials.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
(40 reference statements)
1
25
0
5
Order By: Relevance
“…The second most common reason for surgical intervention during pregnancy in our study was adnexal pathology, including one case of pediculated leiomyoma, the third was cholecystolithiasis [17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 75%
“…The second most common reason for surgical intervention during pregnancy in our study was adnexal pathology, including one case of pediculated leiomyoma, the third was cholecystolithiasis [17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 75%
“…Currently, the main surgical technique in the management of acute appendicitis during pregnancy is yet to be established. The preferred surgical method is based upon the trimester of pregnancy and the surgeon's own preference (3,9,13,24). Our findings indicated that the laparoscopic management of appendicitis was more frequently used in the non-pregnant women than in the pregnant women.…”
Section: Discussionmentioning
confidence: 80%
“…Učestalost je približno jednaka kod trudnica te kod žena koje nisu trudne, a bolest se pojavljuje u otprilike 1/1500 trudnoća, što predstavlja 25 % neopstetričkih zahvata u trudnica. 1 Učestalost varira i tijekom same trudnoće, a pojavnost je u većini slučajeva u drugom tromjesečju. Unatoč činjenici da je akutna upala crvuljka češća tijekom prvog i drugog trimestra, perforacija i pojava komplikacija češće su u trećem trimestru.…”
Section: Incidencija Akutnog Apendicitisa U Trudnoćiunclassified
“…UVOD Upala crvuljka jedna je od najčešćih operacija provođenih na odjelima kirurgije uopće s incidencijom koja varira od 100 do preko 150 slučajeva na 100 000 stanovnika, ovisno o tehnološkoj razvijenosti i geolokalizaciji populacije 1 . U trudnoći apendicitis predstavlja jednu od učestalih neopstetričkih hitnoća.…”
unclassified